Chemical control of the coffee root mealybug Dysmicoccus texensis (Tinsley, 1900) in coffee plants (Coffea arabica L.) - Souza, Júlio César de; Reis, Paulo Rebelles; Ribeiro, Joaquim Afonso; Santa-Cecília, Lenira Viana Costa; Silva, Rogério Antônio (Coffee Science - ISSN 1984-3909, 1970)
The coffee root mealybug Dysmicoccus texensis (Tinsley, 1900) (Hemiptera: Pseudococcidae) lives in colonies in the roots of coffee plants (Coffea spp.) in Brazil. In young plants it destroys the root system, leading eventually to their death. Adult plants bear the attack without suffering damage to their roots, but the losses caused remain unknown. Infestation focuses of the root mealybug occur in new plantations. Although it has been referred to in the literature since the forties, with endemic infestations mainly in São Paulo state, Brazil, efficient control of the coffee root mealybug was only defined from 2000 onwards with the use of neonicotinoids, imidacloprid and thiamethoxam systemic and low toxicity insecticides in water dispersible granular formulation (WG). The objective of this work was to test those insecticides, when applied in liquid form to the plant basis, in several dosages, in the control of the root mealybug. The control efficiency was done through a comparison with systemic insecticides in the granular formulation (GR), applied alone or mixed with systemic fungicides already registered for control of the coffee leaf miner, Leucoptera coffeella (Guérin-Mèneville, 1842) (Lepidoptera: Lyonetiidae), cicada Quesada gigas (Olivier, 1790) (Hemiptera: Cicadidae) and of the rust Hemileia vastatrix Berk. & Br. The products in the liquid form were applied to the base of the plant using a hand back knap sack sprayer endowed with a dosage nipple; the granular products were applied in soil furrows. The results show that the two insecticides cause 100% mortality of the coffee root mealybug, independent of the coffee plant’s age, in a single application.